The Impact Of Performance Management System On Employee Involvement And Interpersonal Trust: A Survey Among Scientists (International Journal of Scientific Research and Management (IJSRM), 2015)
The phenomenon of performance management, which holds a significant place in management literature encompasses crucial decision making processes and outcomes and its potential and possibilities gather momentum with every attempt of research and discourse on the topic, the new insights of which are sure to brighten its pathways of progress. This paper attempts to foresee the impact of performance management system on employee involvement and interpersonal trust. This study intends to empirically validate the mediating role of employee involvement in the relationship between performance management system and interpersonal trust. It is envisaged that this study based on primary data collected from 150 scientists working in nationalized research and development organizations in Kerala and carried out during the time period of January – March 2015 ,will add to our understanding of the link between performance management system, employee involvement and interpersonal trust. Partial Least Squares (PLS) was used to authorize the relationship among the variables. Findings of the study are conferred, together with limitations and suggestions for future research. This empirical study reiterates through its analysis and results that there is significant relationship between performance management system and employee involvement. The study provides a deeper and richer understanding in explaining the relationship between employee involvement and interpersonal trust. Thus performance management system implies employee involvement and interpersonal trust in organization and portrays that employee involvement partially intercedes the relationship between performance management system and interpersonal trust